2014
DOI: 10.1155/2014/372521
|View full text |Cite
|
Sign up to set email alerts
|

Single Ascending Dose Safety and Pharmacokinetics of CDRI-97/78: First-in-Human Study of a Novel Antimalarial Drug

Abstract: Background. CDRI 97/78 has shown efficacy in animal models of falciparum malaria. The present study is the first in-human phase I trial in healthy volunteers. Methods. The study was conducted in 50 healthy volunteers in a single, ascending dose, randomized, placebo-controlled, double blind design. The dose ranges evaluated were from 80 mg to 700 mg. Volunteers were assessed for clinical, biochemical, haematological, radiographic, and electrocardiographic parameters for any adverse events in an in-house facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The Central Drug Research Institute, Lucknow, India, is investigating a new chemical enitity (NCE) trioxane CDRI-97/78, currently in Phase I studies. It has 'triaxone core 'and singlet oxygen to yield a peroxide compound [5].…”
Section: Discussionmentioning
confidence: 99%
“…The Central Drug Research Institute, Lucknow, India, is investigating a new chemical enitity (NCE) trioxane CDRI-97/78, currently in Phase I studies. It has 'triaxone core 'and singlet oxygen to yield a peroxide compound [5].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the in-vitro metabolic study were expressed as the % drug remaining, which was calculated as: % Drug remaining = drug conc: after incubation drug conc: at t = 0 × 100 (2) The % plasma protein binding was calculated as, % Plasma protein binding = Drug conc: analyzed at t = 0 Spiked plasma conc: × 100 (3) It has been reported that 97/78 (prodrug) converts into 97/63 (active metabolite) within a few minutes in biological matrices like plasma [15], thus samples were analyzed for the determination of 97/63, post 97/78 oral dose administration alone and with rifabutin in male and female rats. All the results are expressed as mean values ± SEM, n = 4.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Clinically, Tarning et al described the population pharmacokinetics of PPQ in children affected with uncomplicated falciparum malaria by a two-transit compartment absorption model and a three-compartment distribution model. [10] CDRI 97-78 is predominantly metabolized by rat CYP isoform 3A2 to form 97-63. [3] In a study conducted in Cambodian patients by Hung et al, children were found to have a two-fold higher oral clearance (1.85 L/h/kg) and a shorter terminal half-life (13.5 days) than adults.…”
Section: Introductionmentioning
confidence: 99%
“…[9] CDRI 97-78 has been found to be safe in healthy human volunteers during single ascending dose safety and pharmacokinetic studies. [10] CDRI 97-78 is predominantly metabolized by rat CYP isoform 3A2 to form 97-63. [11] Although, a few methods have been reported for quantification of 97-63, no method is presently available to simultaneously quantify PPQ and 97-63.…”
Section: Introductionmentioning
confidence: 99%